Quantifying the Physical Response to a Contemporary Amateur Boxing Simulation. Issue 4 (April 2018) - Finlay, Mitchell J.; Greig, Matt; Page, Richard M.
Abstract : Abstract: Finlay, MJ, Greig, M, and Page, RM. Quantifying the physical response to a contemporary amateur boxing simulation. J Strength Cond Res 32(4): 1005–1012, 2018—This study examined the physical response to a contemporary boxing-specific exercise protocol (BSEP), based on notational analysis of amateur boxing. Nine male senior elite amateur boxers completed a 3 × 3-minute BSEP, with a 1-minute passive recovery period interspersing each round. Average (HRave ) and peak (HRpeak) heart rates, average (V[Combining Dot Above]O2ave ) and peak oxygen consumptions (V[Combining Dot Above]O2 peak), blood lactate (BLa) concentrations, rating of perceived exertion, and both triaxial and uniaxial PlayerLoad metrics were recorded during the completion of the BSEP. Blood lactate concentration increased significantly in each round (Round 1 = 2.4 ± 1.3 mmol·L −1 ; Round 2 = 3.3 ± 1.7 mmol·L −1 ; Round 3 = 4.3 ± 2.6 mmol·L −1 ). Significantly lower HRave and HRpeak values were found in the first round (HRave : 150 ± 15 b·min −1 ; HRpeak: 162 ± 12 b·min −1 ) when compared with the second (HRave : 156 ± 16 b·min −1 ; HRpeak: 166 ± 13 b·min −1 ) and third (HRave : 150 ± 15 b·min −1 ; HRpeak: 169 ± 14 b·min −1 ). No significant differences were found in any of the V[Combining Dot Above]O2 or PlayerLoad metrics recorded during the BSEP. The BSEP based on notational analysis elicited a fatigue response across rounds, confirming its validity. The BSEP can be used as a training tool for boxing-specific conditioning with implications for reduced injury risk, and to assess the physical response to boxing-specific interventions. Moreover, the BSEP can also be manipulated to suit all levels of participants or training phases, with practical applications in performance monitoring and microcycle periodization.